2022
DOI: 10.1159/000522230
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Screening for Congenital Adrenal Hyperplasia in Denmark: 10 Years of Experience

Abstract: Introduction: Early detection of salt-wasting congenital adrenal hyperplasia (SW-CAH) is important to reduce CAH related morbidity. However, neonatal screening has shown to have a low positive predictive value (PPV), especially among preterm newborns. Here, the Danish CAH screening is evaluated by comparing incidence and morbidity of SW-CAH ten years before and after introduction of screening. Furthermore, sensitivity, specificity and PPV are determined. Methods: All newborns in Denmark born during 1999-2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
2
9
0
1
Order By: Relevance
“…Whilst the retrospective data analysis meant that we did not obtain follow-up samples from these cases, the babies were assumed to be unaffected. These findings are consistent with a recent report from the Danish NBS programme, which reported normal follow-up samples in four babies with mildly elevated 21DF levels on an initial sample [ 20 ]. Similarly, Held et al reported that 21DF concentrations in screening samples from unaffected babies ranged from 0.01 to 2.06 ng/mL (0.03 to 6.10 nmol/L) and overlapped with one confirmed CAH case [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Whilst the retrospective data analysis meant that we did not obtain follow-up samples from these cases, the babies were assumed to be unaffected. These findings are consistent with a recent report from the Danish NBS programme, which reported normal follow-up samples in four babies with mildly elevated 21DF levels on an initial sample [ 20 ]. Similarly, Held et al reported that 21DF concentrations in screening samples from unaffected babies ranged from 0.01 to 2.06 ng/mL (0.03 to 6.10 nmol/L) and overlapped with one confirmed CAH case [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…We recently investigated all newborns born in Denmark diagnosed with CAH in a 10-year period before and after introduction of screening and found a prevalence of SW CAH of 5 per 100,000 newborns before as well as after screening. 7 Here, observing a much longer period, we report a prevalence of SW CAH of 6.4 per 100,000 newborn females and 5.6 per 100,000 newborn males.…”
Section: Discussionmentioning
confidence: 59%
“…Screening for CAH has been implemented in neonatal screening programs in several countries worldwide, with the aim to achieve early identification of newborns with SW CAH to prevent salt-wasting adrenal crisis and reduce mortality. 3 , 18 Since the screening has a very high sensitivity for SW CAH, 7 , 9 prevalence estimates of SW CAH among newborns participating in screening are available from several countries. 3 In screening studies from countries with health care systems comparable to the Danish system, the reported prevalence of SW CAH range from 3.4 to 5.5 per 100,000 newborns (Sweden: 148 cases among ∼2,700,000 newborns 11 ; Netherlands: 114 cases among 2,235,931 newborns 19 ; New Zealand: 40 cases among 1,175,973 newborns 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations